Unusual clinicopathological presentation of nontraumatic cerebral fat embolism: Two-case report. Issue 12 (March 2020) - Lee, Hye Seung; Park, Jeong-Jin; Roh, Hong Gee; Lim, So Dug
Abstract: Rationale: Fat embolism syndrome (FES) is characterized by the classical triad of cerebral, respiratory, and cutaneous manifestations. In contrast, cerebral fat embolism (CFE), corresponding to incomplete pure type FES, is much rarer and usually follows trauma. CFE typically shows a "starfield" pattern on diffusion-weighted magnetic resonance imaging due to the involvement of multiple small arteries. We report 2 unusual cases of CFE that showed a nontraumatic etiology and the involvement of a single dominant cerebral artery. Patient concerns: Case 1 was a 33-year-old woman without a history of trauma who visited the emergency room due to hemiparesis and hemisensory deficits. She was a heavy smoker and had used oral contraceptives for several years. Most importantly, she had 2 experiences of autologous fat grafting 2 months previously. Magnetic resonance angiography (MRA) revealed acute occlusion of the right middle cerebral artery. Case 2 was an 80-year-old man suddenly presented with dizziness, ataxia, and left-sided sensorimotor dysfunction. He had a history of hypertension, untreated atrial fibrillation, and chronic alcoholism. MRA demonstrated the occlusion of the distal basilar artery. Diagnosis: Case 1: Microscopic findings demonstrated variable sized fat vacuoles intermixed with moderate amounts of thrombi. Case 2: Histologically, mature adipocytes were intermingled with fibrin, blood cells, and a fragment of entrapped soft tissue resembling the vessel wall. Intervention: Case 1 and 2 underwent aspirational thrombectomy guided by transfemoral cerebral angiography. Outcome: Case 1 recovered well but Case 2 still suffers from gait ataxia. Lessons: CFE can rarely occur in various nontraumatic conditions, with or without evident etiology. Furthermore, it may not show characteristic clinicopathological manifestations. Therefore, careful follow up of those who have undergone procedures that are likely to trigger FES or who have hemodynamic or hypercoagulable risk factors is needed.